Aspects of culture in second language acquisition and foreign language learning - Arabski, Janusz; Wojtaszek, Adam (Second language learning and teaching, 2011)
In recent years language learning has been increasingly viewed by some SLA researchers as an essentially social-psychological process in which the role of a wider sociocultural context should not be marginalized.  This volume offers a valuable contribution to this growing body of research by providing theoretical considerations and empirical research data on themes such as the development of intercultural communicative competence, the role of English as a lingua franca in intercultural communication, and the place of cultural factors in SLA theorizing, research, second/foreign language teaching and teacher training.  The volume also contains contributions which share the linguistic interest in the culture-related concepts and constructs such as time, modesty, politeness, and respect, discussing the culture-dependent differences in conceptualization and their reflection in particular language forms and linguistic devices